Early Axial Growth Outcomes of Pediatric Patients Receiving Proton Craniospinal Irradiation. Issue 8 (November 2018) - De, Brian; Cahlon, Oren; Sine, Kevin; Mah, Dennis; Hug, Eugen B.; Wolden, Suzanne L.
Abstract : Guidelines on proton craniospinal irradiation (p-CSI) target volume selection in children are lacking. We examined the impact of target volume selection on growth of children receiving p-CSI at a institution. Records of 58 patients who received p-CSI were reviewed. Median age at treatment initiation was 8 years (range, 2 to 18 y). Spinal target volumes included whole vertebral body (WVB) in 67% and partial vertebral body (PVB) in 33%. Height z -scores before and after p-CSI were assessed using Centers for Disease Control and Prevention stature-for-age charts. Maximal Cobb angle and height z -score change were compared for WVB versus PVB p-CSI using a t test. Among 93% of patients with detailed data, median follow-up was 19 months (range, 2 to 58 mo) after radiation therapy initiation. Quantitative growth evaluations were available for 64% of patients. Median change in height z -score was −0.5 (range, −2.1 to +0.7) after treatment, representing a decrease ( P <0.001) in age-adjusted height. WVB patients had significantly greater reduction in height z -score versus PVB patients ( P =0.004) but no difference in Cobb angle change ( P >0.05). Despite reluctance surrounding its use in younger patients, PVB p-CSI was associated with similar spinal curvature and less growth suppression as compared with WVB p-CSI; a trial comparing WVB versus PVB in children may be warranted.